Motivational adaptation in English grammar learning: a mixed-methods study of students during the transition to senior high school - Zhuang, Zhuojun; Wang, Di (Frontiers in Psychology, 2026)
The transition to senior high school represents a critical developmental period where adolescents face increased academic demands that can challenge their psychological motivation. Given the important role of motivation in language learning, this study examines how students adjust their learning motivation during the transition. Drawing on expectancy-value theory (EVT), the mixed-methods study aims to explore senior high school freshmen’s motivational adaptation in English grammar learning during the transition and the factors influencing the process. Pre- and post-semester questionnaires and follow-up interviews were used to examine changes in students’ motivational beliefs and to identify influential factors. Quantitative results showed significant increases in intrinsic value, utility value, and expectancies for success, while attainment value and perceived task difficulty remained stable. Qualitative analysis identified four key influences: students’ affective attitudes, perceived increase in grammar difficulty, targeted instructional support, and perceived self-worth. This study contributes to the understanding of motivational adaptation during high-pressure academic transitions and highlights that well-designed grammar instruction plays a key role in facilitating smoother psychological adjustment during school transitions.